CLINICAL SPECTRUM AND PATIENT CHARACTERISTIC OF CONDYLOMA ACUMINATA: A TWO-YEAR RETROSPECTIVE REVIEW AT DR. MOHAMAD SOEWANDHIE GENERAL HOSPITAL - Suryani Novelita Sutrisno, Christine; Hinda Pramita, Desy; Puspita Dewi, Ita (JURNAL WIDYA MEDIKA, 2025)
Condyloma acuminata (CA), primarily caused by low-risk human papillomavirus (HPV) types 6 and 11, is among the most common sexually transmitted infections (STIs) worldwide. Despite its public health importance, local epidemiological data in Indonesia remain limited. This study aimed to describe the demographic characteristics, lesion distribution, and comorbidities of CA patients in a tertiary dermatology outpatient clinic. A retrospective descriptive study was conducted using electronic medical records of patients with confirmed CA at Dr. Mohamad Soewandhie General Hospital, Surabaya, Indonesia, between January 2023 and December 2024. Extracted variables included demographic characteristics, clinical presentation, and comorbidities. Seventy-five patients met the inclusion criteria, consisting of 38 females (50.7%) and 37 males (49.3%). The majority were adults aged 19–59 years (n=71, 94.7%), with smaller proportions of adolescents (n=3, 4.0%) and elderly patients (n=1, 1.3%). Genital lesions were the predominant manifestation across both sexes, whereas anal lesions occurred more frequently in males. HIV was the most common comorbidity, emphasizing the overlap between CA and other STIs. In conclusion, CA primarily affects young adults in their reproductive years, with HIV co-infection representing a major clinical concern. These findings underscore the importance of early detection, comprehensive STI screening, and consideration of gender-neutral HPV vaccination in Indonesia.